NIZĀR QABBĀNŶ'S POEM AL-ḤUBB WA AL-BITRŪL: A RIFFATERRE SEMIOTIC APPROACH - Husain Miftahul Rizqi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to reveal the collective meaning of the poem Al- Ḥubb wa Al-Bitrūl. The theory used is the semiotic theory of Michael Riffaterre. Riffaterre's semiotic theory offers two methods of reading: heuristic and hermeneutic. The primary data in this study refer directly to the poem Al-Ḥubb wa Al-Bitrūl composed by Nizār Qabbānŷ and written into a book entitled Al-'A'māl Al-Siyāsiyah Al-Kāmilah volume 3. The supporting data in this study is in the form of appropriate data and helps the course of this research. This type of research is descriptive qualitative research. The data collection technique used in this study is the read-and-record technique. That is by carefully reading the research object and then recording the important points in thepoem. The next stage is to perform heuristic and hermeneutic readings of the poem. Theresult of this study was that heuristic readings in the poem were found based on language conventions. The hermeneutic readings are models of sentences in each part of the poem. The sentence model found it is “Mata Tafham?